HUBUNGAN ANTARA PERSEPSI TERHADAP PROFESI POLRI DAN KEPEMIMPINAN TRANSFORMASIONAL DENGAN EFEKTIVITAS KINERJA Penelitian pada Anggota Kesatuan Polisi Lalu Lintas Polda DIY YOGYAKARTA - , WAHYU HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the relationship between perceptions of the police profession and the effectiveness performance of transformational leadership. The study was conducted at the Police Traffic Unit Yogyakarta. The study was conducted with a quantitative approach. 0,473, p=0,029<0,05). The research sample was done by purposive sampling by considering the condition of the sample is homogeneous, and the willingness or availability of research subjects. The number of samples used as many as 90 were taken from Bantul Police Traffic Unit, Police Traffic Unit Gunungkidul Kulonprogo Police Traffic Unit, Sleman Police Traffic Unit, Traffic Unit Police Poltabes Yogyakarta, Yogyakarta police Ditlantas, respectively 15. Measurements performed with the instrument variable semantic differential scale with interval score of 0 to 10. Research instruments are qualified validity and reliability. Data analysis was performed using multiple linear regression. The results of this study show the empirical evidence: (1) Transformational Leadership and Professional Perceptions of Police and collectively significantly related to Performance Effectiveness (F = 15.571, p = 0.000 <0.05), (2) Perceptions of the Police Profession have relationships that are positive and significant with Performance Effectiveness ( Based on the value of the product moment correlation, it can be said the relationship between the perception of the effectiveness of the Police Profession relatively moderate performance, (3) Transformational leadership has a relationship that is positive and significant with Performance Effectiveness (b1 = 0.283 p = 0.029 <0.05). Based on the correlation value momentnya product, we can conclude with the relationship between Transformational Leadership Effectiveness Performance relatively moderate, (4) The coefficient of determination of 24.7%, indicating that the level of performance of members of the Police Effectiveness is determined by 24.7% and the Perception of Transformational Leadership the police profession, while 75.3% were prescribed other variables that are not included in this study.